A method for preparing a liquid-conducting glass substrate and a heating element
By using a combined structure of a liquid-guiding glass substrate and a heating film in the heating body of the electronic atomization device, the liquid-guiding micropores are formed by using laser induction and corrosion technology, the problems of unsatisfactory atomization effect and high cost in the prior art are solved, and efficient and low-cost atomization effect are achieved.
Patent Information
- Application Number
- CN202110757477.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-07-05
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2041-07-05
AI Technical Summary
The atomization effect of the existing electronic atomization device is not ideal, and the design of the heating element is problematic of high cost, power mismatch and high risk of liquid leakage.
The combined structure of the liquid-guiding glass substrate and the heating film is adopted to form liquid-guiding micropores with different pore sizes through laser induction and corrosion technology, accurately control the porosity, and form a low resistivity heating film on the surface of the liquid-guiding glass substrate.
It realizes efficient atomization of the heating body, is suitable for large-scale standardized production, reduces costs, and improves the service life and atomization effect of the equipment.
Smart Images

Figure CN114794566B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of atomizers, and in particular to a method for preparing a liquid-conducting glass substrate and a heating element. Background Art
[0002] A typical electronic atomization device consists of a heating element, a battery, a control circuit and other parts. The heating element is the core component of the electronic atomization device, and its characteristics determine the atomization effect and user experience of the electronic atomization device.
[0003] The existing heating elements are mainly cotton core heating elements and ceramic heating elements. Cotton core heating elements are mostly spring-shaped metal heating wires wrapped around cotton ropes or fiber ropes; the liquid aerosol to be atomized generates a matrix that is absorbed by both ends of the cotton rope and then transferred to the central metal heating wire for heating and atomization. Ceramic heating elements are mostly formed with a heating film on the surface of a porous ceramic body, which plays the role of guiding and storing liquid.
[0004] With the advancement of technology, users have higher and higher requirements on the atomization effect of electronic atomization devices. In order to meet the needs of users, it is necessary to provide a heating element with better atomization effect. Summary of the invention
[0005] In view of the above problems, the present application provides a method for manufacturing a heating element to solve the problem of how to meet the user's demand for atomization effect in the prior art.
[0006] In order to solve the above technical problems, the technical solution provided in the present application is: to provide a method for manufacturing a heating element, comprising: performing a first laser induction and corrosion on a substrate to be processed to form a prefabricated hole of a first micropore, the prefabricated hole having a prefabricated aperture; performing a second laser induction and corrosion on the substrate to be processed to form a second micropore, the second micropore having a second aperture, wherein the second corrosion process of the substrate to be processed expands the prefabricated aperture to the first aperture, and further, the prefabricated hole is transformed into the first micropore, thereby obtaining a liquid-conducting glass substrate with liquid-conducting micropores of different apertures.
[0007] The substrate to be processed includes a first surface and a second surface opposite to and parallel to the first surface, and the first micropores and the second micropores are straight through holes penetrating and perpendicular to the first surface and the second surface.
[0008] The step of performing a first laser induction and etching on the substrate to be processed to form a prefabricated hole of the first micropore comprises: performing laser induction on the substrate to be processed according to the distribution of micropores of the first aperture; performing a first etching on the substrate subjected to the first laser induction, wherein the etching time is the total etching time (N) required for the first aperture minus the etching time (M) required for the second aperture;
[0009] The step of performing a second laser induction and etching on the substrate to be processed to form a second micropore includes: performing laser induction on the substrate to be processed according to the distribution of micropores of a second aperture, and performing a second etching on the substrate subjected to the second laser induction for a time equal to the etching time (M) required for the second aperture.
[0010] The step of performing a first laser induction and etching on the substrate to be processed to form a prefabricated hole of the first microhole comprises: forming a prefabricated hole array including a plurality of prefabricated holes with prefabricated apertures;
[0011] The step of performing a second laser induction and etching on the substrate to be processed to form second microholes includes: forming a second microhole array including a plurality of second microholes with a second aperture and a first microhole array including a plurality of first microholes with a first aperture.
[0012] The ratio of the thickness of the liquid-conducting glass substrate to the pore size of the liquid-conducting micropores is 20:1-3:1.
[0013] The ratio of the thickness of the liquid-conducting glass substrate to the pore size of the liquid-conducting micropores is 15:1-5:1.
[0014] The ratio of the hole center distance between two adjacent liquid-conducting micropores to the hole diameter of the liquid-conducting micropores is 3:1-1.5:1.
[0015] Wherein, the substrate to be processed is glass.
[0016] Wherein, the substrate to be processed is glass, and the glass is one or more of borosilicate glass, quartz glass and photosensitive lithium aluminosilicate glass.
[0017] To solve the above technical problems, the second technical solution provided in this application is: to provide a method for preparing a heating element, the preparation method comprising: preparing a liquid-conducting glass substrate, the preparation method of the liquid-conducting glass substrate being any of the preparation methods mentioned above; and forming a heating film on the first surface of the liquid-conducting glass substrate.
[0018] Among them, the step of forming a heating film on the first surface of the liquid-conducting glass substrate includes: forming a heating film with a resistance of 0.5 ohms to 2 ohms and a thickness of 200 nanometers to 5 microns by physical vapor deposition or chemical vapor deposition; the material of the heating film is aluminum, copper, silver, gold or their alloys.
[0019] Among them, after the step of forming a heating film on the first surface of the liquid-conducting glass substrate, it includes: forming a protective film with a thickness of 100 nanometers to 1000 nanometers on the surface of the heating film away from the liquid-conducting glass substrate by physical vapor deposition or chemical vapor deposition; the material of the protective film is one or any combination of stainless steel, nickel-chromium-iron alloy, and nickel-based corrosion-resistant alloy.
[0020] Among them, the step of forming a heating film on the first surface of the liquid-conducting glass substrate includes: forming a heating film with a resistance of 0.5 ohms to 2 ohms and a thickness of 5 microns to 100 microns by printing or chemical vapor deposition; the material of the heating film is one of nickel-chromium alloy, nickel-chromium-iron alloy, iron-chromium-aluminum alloy, nickel, platinum and titanium.
[0021] Among them, after the step of forming a heating film on the first surface of the liquid-conducting glass substrate, the step includes: forming a protective film with a thickness of 5 microns to 20 microns on the surface of the heating film away from the liquid-conducting glass substrate by printing or chemical vapor deposition; the material of the protective film is stainless steel.
[0022] Beneficial effects of the present application: Different from the prior art, the heating element in the present application includes a liquid-conducting glass substrate and a heating film; the specific preparation method includes: performing a first laser induction and corrosion on the substrate to be processed to form a prefabricated hole of the first micropore, and the prefabricated hole has a prefabricated aperture; performing a second laser induction and corrosion on the substrate to be processed to form a second micropore, and the second micropore has a second aperture, wherein the process of performing the second corrosion on the substrate to be processed expands the prefabricated aperture to the first aperture, and the prefabricated hole is transformed into the first micropore, thereby obtaining a liquid-conducting glass substrate with liquid-conducting micropores of different apertures; forming a heating film on the first surface of the liquid-conducting glass substrate. Through the above process, the porosity of the heating element can be accurately controlled in batch production, the fluctuation range is small, and the heating power can be accurately matched, thereby achieving a better atomization effect, which is suitable for large-scale standardized production. In addition, since the process of performing the second corrosion on the substrate to be processed expands the first micropore from the prefabricated aperture to the first aperture, compared with separately preparing the second micropore with the second aperture and the first micropore with the first aperture, the method has a simple process and low cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0024] Figure 1 It is a schematic diagram of the structure of the electronic atomization device provided by the present application;
[0025] Figure 2 It is a structural schematic diagram of the atomization assembly provided by the present application;
[0026] Figure 3 It is a schematic diagram of the structure of the heating element provided by the present application;
[0027] Figure 4 yes Figure 3A schematic diagram of the structure of a dense matrix in a heating element is provided;
[0028] Figure 5a yes Figure 3 A schematic structural diagram of a first embodiment of micropores in a dense matrix is provided;
[0029] Figure 5b yes Figure 3 A schematic diagram of the structure of a second embodiment of micropores in a dense matrix is provided;
[0030] Figure 5c yes Figure 3 A schematic structural diagram of a third embodiment of micropores in a dense matrix is provided;
[0031] Figure 5d yes Figure 3 A schematic structural diagram of a fourth embodiment of micropores in a dense matrix is provided;
[0032] Figure 6a yes Figure 3 A schematic diagram of a top view of a first embodiment of a dense matrix is provided;
[0033] Figure 6b yes Figure 3 A schematic top view of a second embodiment of a dense matrix is provided;
[0034] Figure 7 yes Figure 6b A schematic diagram of the manufacturing process of the dense matrix is provided;
[0035] Figure 8a for Figure 7 A schematic diagram of a top view of the structure of step S1;
[0036] Figure 8b for Figure 7 A side view structural diagram of step S1;
[0037] Figure 8c for Figure 7 A schematic diagram of a top view of the structure of step S2;
[0038] Figure 8d for Figure 7 A side view structural diagram of step S2;
[0039] Figure 9a It is a schematic diagram of a top view structure when the heating film in the heating element provided by the present application is a thick film;
[0040] Figure 9b yes Figure 3 A schematic diagram of the top view of the heating element provided;
[0041] Fig.10It is a schematic structural diagram of the heating element provided by the present application, which includes a protective film and the heating film is a thin film;
[0042] Fig.11 It is a schematic diagram of a top view structure in which the heating element provided by the present application includes a protective film and the heating film is a thick film;
[0043] Fig.12 It is a schematic diagram of the structure of the atomization assembly provided by the present application including a loose matrix;
[0044] Fig.13 is a SEM image of an embodiment of the heating film provided by the present application;
[0045] Fig.14 This is a comparison chart of the amount of atomized aerosol of the heating element of the present application and the traditional porous ceramic heating element;
[0046] Fig.15 It is a failure diagram of the heating film in the heating element provided by the present application;
[0047] Fig.16 yes Fig.15 Provide SEM and EDS images of heating film failure diagram;
[0048] Fig.17 This is a relationship diagram between the life of the heating film and the thickness of the protective film in the heating element provided by the present application;
[0049] Fig.18 It is a schematic diagram of the wet burning experiment of the heating element provided in this application;
[0050] Fig.19 is a graph showing the relationship between the thickness of the dense matrix / pore diameter of the heating element and the amount of atomization provided by the present application;
[0051] Fig. 20 This is the relationship between the atomization temperature and heating power of the traditional porous ceramic heating element;
[0052] Fig.21 It is a relationship diagram between the atomization temperature and the heating power of the heating element provided in the present application;
[0053] Fig. 22 It is a relationship diagram between the atomization temperature of the heating element and the puffing time provided in the present application. DETAILED DESCRIPTION
[0054] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0055] The terms "first", "second", "third" in this application are only used for descriptive purposes, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of indicated technical features. Thus, the features defined as "first", "second", "third" can expressly or implicitly include at least one of the features. In the description of this application, the meaning of "multiple" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined. In the embodiments of this application, all directional indications (such as up, down, left, right, front, back...) are only used to explain the relative position relationship, movement, etc. between the components under a certain specific posture (as shown in the accompanying drawings). If the specific posture changes, the directional indication also changes accordingly. In addition, the terms "including" and "having" and any of their variations are intended to cover non-exclusive inclusions. For example, a process, method, system, product or device comprising a series of steps or units is not limited to the steps or units listed, but optionally also includes steps or units that are not listed, or optionally also includes other steps or units inherent to these processes, methods, products or devices.
[0056] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0057] See also Figure 1 , Figure 1 It is a schematic diagram of the structure of the electronic atomization device provided in this application.
[0058] The electronic atomization device can be used for atomization of liquid substrates. The electronic atomization device includes an atomization component 1 and a power supply component 2 that are interconnected. The atomization component 1 is used to store liquid aerosol-generating substrates and atomize the aerosol-generating substrates to form an aerosol that can be inhaled by users. The liquid aerosol-generating substrate can be a liquid substrate such as a liquid medicine, a plant leaf liquid, etc.; the atomization component 1 can be specifically used in different fields, such as medical treatment, electronic aerosolization, etc. The power supply component 2 includes a battery (not shown), an airflow sensor (not shown), and a controller (not shown), etc.; the battery is used to power the atomization component 1 so that the atomization component 1 can atomize the substrate to be atomized to form an aerosol; the airflow sensor is used to detect airflow changes in the electronic atomization device, and the controller starts the electronic atomization device according to the airflow changes detected by the airflow sensor. The atomization component 1 and the power supply component 2 can be an integrated arrangement or a detachable connection, and are designed according to specific needs.
[0059] See also Figure 2 , Figure 2 It is a structural schematic diagram of the atomization assembly provided in this application.
[0060] The atomization component 1 includes a liquid storage chamber 10, a heating element 11, a suction nozzle 12, and a mist outlet channel 13. The liquid storage chamber 10 is used to store liquid aerosol generating substrates, and the heating element 11 is used to atomize the aerosol generating substrates in the liquid storage chamber 10. In the present embodiment, a lower liquid channel 14 is formed between the liquid storage chamber 10 and the heating element 11 to guide the liquid in the liquid storage chamber 10 to the heating element 11; in another embodiment, the heating element 11 can also be directly exposed to the liquid storage chamber 10 to atomize the liquid in the liquid storage chamber 10. The aerosol atomized by the heating element 11 passes through the mist outlet channel 13 to the suction nozzle 12 to be inhaled by the user. Among them, the heating element 11 is electrically connected to the power supply component 2 to atomize the aerosol generating substrate.
[0061] At present, the heating element 11 commonly used are cotton core heating element and porous ceramic heating element. The structure of the cotton core heating element is mostly a spring-shaped metal heating wire wrapped with a cotton rope or a fiber rope; the spring-shaped metal heating wire needs to play a structural support role in the cotton core heating element structure. In order to achieve sufficient strength, the diameter of the metal heating wire is usually hundreds of microns; the liquid aerosol to be atomized generates a matrix that is absorbed by both ends of the cotton rope or the fiber rope, and then transmitted to the central metal heating wire to be heated and atomized. One structure of the porous ceramic heating element is that the spring-shaped metal heating wire is embedded in a cylindrical porous ceramic body; the porous ceramic body plays the role of guiding and storing liquid. Another structure of the porous ceramic heating element is to print a metal thick film slurry on the porous ceramic body, and then form a metal wire on the porous ceramic body after high-temperature sintering; because the pore size distribution of the porous ceramic surface ranges from 1 micron to 100 microns, the roughness of the porous ceramic surface is relatively large. In order to form a continuous and stable metal film wire, the thickness of the metal film wire is usually more than 100 microns.
[0062] Porous ceramic heaters are becoming more and more popular in the market due to their high temperature stability and relative safety. The common structure of porous ceramic heaters is to print metal thick film wires on the surface of porous ceramics. The materials of the metal thick film wires of existing electronic atomization devices usually select high-resistivity nickel-chromium alloys, nickel-chromium-iron alloys, iron-chromium-aluminum alloys and other materials. When the metal thick film wires repeatedly heat the liquid aerosol to generate a matrix, heavy metal ions are often detected in the aerosol, such as excessive nickel and chromium. The accumulation of heavy metal ions will cause damage to human organs such as the lungs, liver, and kidneys, which will bring huge safety hazards to users.
[0063] In addition, for the above-mentioned structure of the cotton core heating element and the porous ceramic heating element, when power is turned on, the metal heating wire or the metal thick film conductor is heated, and the heat is transferred to the liquid in the cotton rope or the porous ceramic body, so that the liquid is heated and atomized. Since the metal heating wire or the metal thick film conductor is a dense entity, when power is turned on, the metal heating wire or the metal thick film conductor needs to be heated first, and only the liquid near the metal heating wire or the metal thick film conductor is directly heated by the metal heating wire or the metal thick film conductor, and the liquid far away needs to be heated and atomized by the heat transferred by the cotton rope or the porous ceramic body. The energy provided by the battery needs to heat the metal heating wire or the metal thick film conductor, and also needs to heat the entire liquid transmission medium. This heating method has the disadvantage of low atomization efficiency.
[0064] The power of existing electronic atomization devices does not exceed 10 watts, and the power is usually 6 watts to 8.5 watts. The voltage range of the battery used in existing electronic atomization devices is 2.5 volts to 4.4 volts. For closed electronic atomization devices (electronic atomization devices that do not require users to inject the atomized matrix themselves), the voltage range of the battery used is 3 volts to 4.4 volts.
[0065] The inventor of the present application has found that, since the surface of the liquid-conducting substrate made of dense materials such as glass is smooth, a continuous and stable metal heating film can be deposited on the surface of the liquid-conducting substrate by physical vapor deposition or chemical vapor deposition, and the thickness of the metal heating film is within the range of a few microns or nanometers. This can not only miniaturize the heating element 11, but also save heating film materials.
[0066] However, the inventors of the present application have found that, compared with existing cotton core heating elements and porous ceramic heating elements, the liquid-conducting substrate made of dense materials such as glass has a shorter liquid supply channel and a faster liquid supply speed, but a greater risk of liquid leakage. Therefore, the preparation of the heating element 11 using a liquid-conducting substrate made of dense materials such as glass often requires a higher sealing design for the atomizing component 1, which increases the difficulty and cost of preparing the atomizing component 1. Moreover, even if a structure such as a liquid storage tank is designed in the atomizing component 1 to collect the leaked liquid and prevent the leaked liquid from flowing out of the atomizing component 1, the utilization rate of the aerosol generation matrix is relatively low.
[0067] Furthermore, the inventors of the present application have found that due to the high resistivity of existing nickel-chromium alloys, nickel-chromium-iron alloys, iron-chromium-aluminum alloys and other materials, the resistance of the heating film will increase significantly if the thickness of the heating film is reduced to a few microns or less under the same shape. For example, if the thickness of the heating film is reduced from 100 microns to 10 microns, the resistance increases 10 times; if the power of the heating element 11 is to be kept unchanged, the voltage of the battery needs to be increased, which will lead to an increase in the cost of the electronic atomization device; moreover, such a heating element 11 cannot match the voltage of the battery in the power supply assembly 2 of the current electronic atomization device, resulting in inconvenience for consumers.
[0068] Based on the problems existing in the existing heating elements, the present application provides a heating element 11 to solve the above problems. The structure of the heating element 11 of the present application is introduced in detail below.
[0069] See also Figure 3 and Figure 4 , Figure 3 is a schematic diagram of the structure of the heating element provided in this application, Figure 4 yes Figure 3 A schematic diagram of the structure of a dense matrix in a heating element is provided.
[0070] The heating element 11 includes a dense matrix 111 and a heating film 112. The dense matrix 111 includes a first surface and a second surface 1112 opposite to the first surface 1111; a plurality of micropores 113 are provided on the dense matrix 111, and the micropores 113 are through holes, and the micropores 113 are used to guide the aerosol generating matrix to the first surface 1111. The micropores 113 have a capillary effect. The heating film 112 is formed on the first surface 1111; the resistance of the heating film 112 at room temperature is 0.5 ohms-2 ohms, wherein the room temperature is 25°C. It can be understood that the dense matrix 111 plays a structural support role, and the heating film 112 in the heating element 11 is electrically connected to the power supply assembly 2. When the power of the electronic atomization device is 6W-8.5W and the voltage range of the battery is 2.5V-4.4V, in order to achieve the working resistance of the battery, the resistance range of the heating film 112 of the heating element 11 at room temperature is 0.5 ohm-2 ohm.
[0071] The present application provides a plurality of micropores 113 with capillary force on the dense matrix 111, so that the porosity of the heating element 11 can be precisely controlled to improve the consistency of the product. That is to say, in batch production, the porosity of the dense matrix 111 in the heating element 11 is basically consistent, and the thickness of the heating film 112 formed on the dense matrix 111 is uniform, so that the atomization effect of the electronic atomization devices produced in the same batch is consistent.
[0072] The aerosol-generating matrix in the liquid storage chamber 10 reaches the dense matrix 111 of the heating element 11 through the lower liquid channel 14, and the aerosol-generating matrix is guided to the first surface 1111 of the dense matrix 111 by the capillary force of the micropores 113 on the dense matrix 111, so that the aerosol-generating matrix is atomized by the heating film 112; that is, the micropores 113 are connected to the liquid storage chamber 10 through the lower liquid channel 14. The material of the dense matrix 111 can be glass or dense ceramic; when the dense matrix 111 is glass, it can be one of ordinary glass, quartz glass, borosilicate glass or photosensitive lithium aluminosilicate glass.
[0073] Compared with the existing cotton core heating element and porous ceramic heating element, the heating element 11 with a thin sheet structure with micropores provided in the present application has a shorter liquid supply channel and a faster liquid supply speed, but a greater risk of liquid leakage. Therefore, the inventor of the present application studied the influence of the ratio of the thickness of the dense matrix 111 to the aperture of the micropore 113 on the liquid conduction of the heating element 11. It was found that increasing the thickness of the dense matrix 111 and reducing the aperture of the micropore 113 can reduce the risk of liquid leakage but also reduce the liquid supply rate, while reducing the thickness of the dense matrix 111 and increasing the aperture of the micropore 113 can increase the liquid supply rate but increase the risk of liquid leakage, which are contradictory. For this reason, the present application designs the thickness of the dense matrix 111, the aperture of the micropore 113, and the ratio of the thickness of the dense matrix 111 to the aperture of the micropore 113, so that the heating element 11 can achieve sufficient liquid supply and prevent liquid leakage when the power is 6 watts to 8.5 watts and the voltage is 2.5 volts to 4.4 volts. The thickness of the dense matrix 111 is the distance between the first surface 1111 and the second surface 1112 .
[0074] In addition, the inventors of the present application studied the ratio of the center distance between adjacent micropores 113 to the pore diameter of the micropores 113, and found that if the ratio of the center distance between adjacent micropores 113 to the pore diameter of the micropores 113 is too large, the strength of the dense matrix 111 is relatively large and it is easy to process, but the porosity is too small, which easily leads to insufficient liquid supply; if the ratio of the center distance between adjacent micropores 113 to the pore diameter of the micropores 113 is too small, the porosity is relatively large, the liquid supply is sufficient, but the strength of the dense matrix 111 is relatively small and it is not easy to process; for this reason, the present application also designs the ratio of the center distance between adjacent micropores 113 to the pore diameter of the micropores 113, so as to improve the strength of the dense matrix 111 as much as possible while meeting the liquid supply capacity.
[0075] The following description assumes that the material of the dense matrix 111 is glass.
[0076] Specifically, the first surface 1111 and the second surface 1112 both include smooth surfaces, and the first surface 1111 is a plane. That is, the first surface 1111 of the dense matrix 111 is a smooth surface and a plane, and the heating film 112 is formed on the first surface 1111. The first surface 1111 is a smooth surface, which is conducive to the deposition of metal materials into films with a small thickness.
[0077] In one embodiment, the first plane 1111 and the second surface 1112 of the dense matrix 111 are both smooth surfaces and planes, and the first surface 1111 and the second surface 1112 of the dense matrix 111 are arranged in parallel; the micropore 113 runs through the first surface 1111 and the second surface 1112, the axis of the micropore 113 is perpendicular to the first surface 1111 and the second surface 1112, and the cross section of the micropore 113 is circular; at this time, the thickness of the dense matrix 111 is equal to the length of the micropore 113. It can be understood that the second surface 1112 is parallel to the first surface 1111, and the micropore 113 runs from the first surface 1111 to the second surface 1112, so that the production process of the dense matrix 111 is simple and the cost is reduced. The thickness of the dense matrix 111 is the distance between the first surface 1111 and the second surface 1112. The micropore 113 can be a straight through hole with uniform pore size or a straight through hole with uneven pore size, as long as the range of variation of the pore size is within 50%. For example, due to the limitation of the manufacturing process, the micropore 113 opened on the glass by laser induction and etching usually has a large aperture at both ends and a small aperture in the middle. Therefore, it is sufficient to ensure that the aperture of the middle part of the micropore 113 is not less than half of the aperture of the two end ports.
[0078] In another embodiment, the first surface 1111 of the dense matrix 111 is a smooth surface and a plane, so as to facilitate the deposition of the metal material into a film with a small thickness. The second surface 1112 of the dense matrix 111 is a smooth surface, and the second surface 1112 can be a non-planar surface, such as an inclined surface, a curved surface, a serrated surface, etc. The second surface 1112 can be designed according to specific needs, and the micropores 113 only need to pass through the first surface 1111 and the second surface 1112.
[0079] The following introduces the thickness of the dense matrix 111, the ratio of the thickness of the dense matrix 111 to the aperture of the micropores 113, and the ratio of the center distance between two adjacent micropores 113 to the aperture of the micropores 113 when the material of the dense matrix 111 is glass, and the first surface 1111 and the second surface 1112 of the dense matrix 111 are both smooth planes and are arranged in parallel.
[0080] The thickness of the dense matrix 111 is 0.1 mm-1 mm. When the thickness of the dense matrix 111 is greater than 1 mm, the liquid supply demand cannot be met, resulting in a decrease in the amount of aerosol, and the heat loss caused is large, and the cost of setting the micropores 113 is high; when the thickness of the dense matrix 111 is less than 0.1 mm, the strength of the dense matrix 111 cannot be guaranteed, which is not conducive to improving the performance of the electronic atomization device. Preferably, the thickness of the dense matrix 111 is 0.2 mm-0.5 mm. The aperture of the micropores 113 on the dense matrix 111 is 1 micron-100 microns. When the aperture of the micropore 113 is less than 1 micron, the liquid supply demand cannot be met, resulting in a decrease in the amount of aerosol; when the aperture of the micropore 113 is greater than 100 microns, the aerosol generation matrix is easy to flow out of the micropore 113 to the first surface 1111 to cause leakage, resulting in a decrease in atomization efficiency. Preferably, the aperture of the micropore 113 is 20 microns-50 microns. It is understandable that the thickness of the dense matrix 111 and the pore size of the micropores 113 are selected according to actual needs.
[0081] The ratio of the thickness of the dense matrix 111 to the pore size of the micropores 113 is 20:1-3:1; preferably, the ratio of the thickness of the dense matrix 111 to the pore size of the micropores 113 is 15:1-5:1 (see Fig.19 , it is found through experiments that when the ratio of the thickness of the dense matrix 111 to the pore size of the micropores 113 is 15:1-5:1, it has a better atomization effect). When the ratio of the thickness of the dense matrix 111 to the pore size of the micropores 113 is greater than 20:1, the aerosol generation matrix supplied by the capillary force of the micropores 113 is difficult to meet the atomization demand of the heating element 11, which is not only easy to cause dry burning, but also the amount of aerosol generated by a single atomization decreases; when the ratio of the thickness of the dense matrix 111 to the pore size of the micropores 113 is less than 3:1, the aerosol generation matrix is easy to flow out of the micropores 113 to the first surface 1111, the aerosol generation matrix is wasted, resulting in a decrease in atomization efficiency, and then a decrease in the total aerosol amount.
[0082] The ratio of the center distance between two adjacent micropores 113 to the pore size of the micropore 113 is 3:1-1.5:1, so that the micropores 113 on the dense matrix 111 can improve the strength of the dense matrix 111 as much as possible while satisfying the liquid supply capacity; preferably, the ratio of the center distance between two adjacent micropores 113 to the pore size of the micropore 113 is 3:1-2:1; more preferably, the ratio of the center distance between two adjacent micropores 113 to the pore size of the micropore 113 is 3:1-2.5:1.
[0083] In a specific embodiment, preferably, the ratio of the thickness of the dense matrix 111 to the pore size of the micropore 113 is 15:1-5:1, and the ratio of the center distance between two adjacent micropores 113 to the pore size of the micropore 113 is 3:1-2.5:1.
[0084] See also Figure 5a , Figure 5b , Figure 5c and Figure 5d , Figure 5a yes Figure 3 A schematic diagram of the structure of the first embodiment of the micropores in the dense matrix is provided, Figure 5b yes Figure 3 A schematic diagram of the structure of the second embodiment of the dense matrix micropores provided, Figure 5c yes Figure 3 A schematic diagram of the structure of the third embodiment of the dense matrix micropores provided, Figure 5d yes Figure 3 A schematic structural diagram of a fourth embodiment of micropores in a dense matrix is provided.
[0085] In other embodiments, the micropores 113 may also have other structures, see Figure 5a , Figure 5b , Figure 5c and Figure 5d The extension direction of the micropores 113 is perpendicular to the thickness direction of the dense matrix 111. Specifically, the longitudinal section of the micropores 113 may be a rectangle (eg Figure 5a As shown), trapezoidal (as Figure 5b As shown), dumbbell-shaped with large ends and a small middle (as shown Figure 5c In another embodiment, the extension direction of the micropore 113 forms an angle with the thickness direction of the dense matrix 111, and the angle ranges from 80 degrees to 90 degrees; when the longitudinal section of the micropore 113 is a rectangle, the structure is as shown Figure 5d As shown. Since the micropores 113 are arranged in a regular geometric shape, the volume of the micropores 113 in the heating element 11 can be calculated, and thus the porosity of the entire heating element 11 can also be calculated, so that the consistency of the porosity of the heating elements 11 of similar products can be well guaranteed.
[0086] See also Figure 6a and Figure 6b , Figure 6a yes Figure 3 A schematic diagram of a top view of a first embodiment of a dense matrix is provided, Figure 6b yes Figure 3 A schematic top view of the structure of a second embodiment of the dense matrix is provided.
[0087] Specifically, the dense matrix 111 is a regular shape, such as a rectangular plate, a circular plate, etc. In this embodiment, the plurality of micropores 113 provided on the dense matrix 111 are arranged in an array; that is, the plurality of micropores 113 provided on the dense matrix 111 are regularly arranged, and the hole center distances between adjacent micropores 113 in the plurality of micropores 113 are the same. Optionally, the plurality of micropores 113 are arranged in a rectangular array; or the plurality of micropores 113 are arranged in a circular array; or the plurality of micropores 113 are arranged in a hexagonal array. Among them, the apertures of the plurality of micropores 113 can be the same or different, and are designed according to needs.
[0088] In one embodiment, the dense matrix 111 is in the shape of a rectangular plate, and the plurality of micropores 113 disposed on the dense matrix 111 have the same shape and aperture and are arranged in a rectangular array, such as Figure 6a shown.
[0089] In another embodiment, the dense matrix 111 is in the shape of a rectangular plate, and the first surface 1111 of the dense matrix 111 includes a first aperture micropore array area 1113 and a second aperture micropore array area 1114, the aperture of the micropores 113 of the second aperture micropore array area 1114 is different from the aperture of the micropores 113 of the first aperture micropore array area 1113, and the shape of the micropores 113 of the second aperture micropore array area 1114 is the same as the shape of the micropores 113 of the first aperture micropore array area 1113; the micropores 113 of the second aperture micropore array area 1114 and the micropores 113 of the first aperture micropore array area 1113 are arranged in a rectangular array; the first aperture micropore array area 1113 is located on both sides of the second aperture micropore array area 1114, and the aperture of the micropores 113 of the second aperture micropore array area 1114 is smaller than the aperture of the micropores 113 of the first aperture micropore array area 1113, such as Figure 6b It is understood that the second aperture micropore array area 1114 may be located on both sides of the first aperture micropore array area 1113, the aperture of the micropores 113 of the second aperture micropore array area 1114 is smaller than the aperture of the micropores 113 of the first aperture micropore array area 1113, and the first aperture micropore array area 1113, the second aperture micropore array area 1114 and the micropores 113 disposed therein may be designed as required.
[0090] In other embodiments, the axis of the micropore 113 is not perpendicular to the first surface 1111 and the second surface 1112. One end opening of the micropore 113 is located on the first surface 1111, and the other end opening of the micropore 113 can be located on a third surface (not shown) connecting the first surface 1111 and the second surface 1112; or, the other end opening of the micropore 113 is located on the second surface 1112, and the micropore 113 extends in a curve; the structure of the micropore 113 can be designed as needed, and the aerosol generating substrate can be guided to the first surface 1111 by its capillary force.
[0091] See also Figure 7 , Figure 7 yes Figure 6b A schematic diagram of the process flow for manufacturing a dense matrix is provided. Figure 8a for Figure 7 A schematic diagram of a top view of the structure of step S1; Figure 8b for Figure 7 A side view structural diagram of step S1; Figure 8c for Figure 7 A schematic diagram of a top view of the structure of step S2; Figure 8d for Figure 7 Schematic diagram of the side view structure of step S2.
[0092] In one embodiment, the dense matrix is glass, which is called a liquid-conducting glass matrix. The manufacturing method of the liquid-conducting glass matrix includes the following steps:
[0093] Step S1: performing the first laser induction and etching on the substrate to be processed to form a prefabricated hole of the first microhole.
[0094] For details, see Figure 8a-8b A substrate 111a to be processed is provided, the substrate 111a to be processed includes a first surface 1111a and a second surface 1111b opposite to the first surface 1111a, a first laser induction is performed on the substrate 111a to be processed, and the substrate 111a to be processed after the first laser induction is immersed in a corrosion solution to form a preformed hole of a first micropore 113a. The preformed hole of the first micropore 113a has a preformed aperture, and the preformed hole passes through the first surface 1111a and the second surface 1111b.
[0095] After step S1 , a first micro-hole array 113 c including a plurality of pre-formed holes with pre-formed hole diameters is formed on the substrate 111 a to be processed.
[0096] Step S2: performing a second laser induction and etching on the substrate to be processed to form a second microhole having a second aperture, wherein the second etching process on the substrate to be processed expands the prefabricated hole of the first microhole from the prefabricated aperture to the first aperture.
[0097] For details, see Figure 8c-8d, the substrate 111a to be processed is subjected to a second laser induction according to the second aperture, and the substrate 111a to be processed after the second laser induction is immersed in a corrosion solution to form a second micropore 113b, and the second micropore 113b has a second aperture, wherein the second etching process of the substrate 111a to be processed causes the prefabricated hole of the first micropore 113a to be expanded from the prefabricated aperture to the first aperture, and the first micropore 113a penetrates the first surface 1111a and the second surface 1111b, thereby obtaining a liquid-conducting glass substrate 116 with liquid-conducting micropores 113 with different apertures.
[0098] After step S2 , a second micropore array 113 d including a plurality of second micropores 113 b having a second pore size and a first micropore array 113 c including a plurality of first micropores 113 a having a first pore size are formed on the liquid-conducting glass substrate 116 .
[0099] In a specific embodiment, in order to control the pore sizes of the first micropores 113a and the second micropores 113b, the method for manufacturing the dense matrix includes:
[0100] S11: performing laser induction on the substrate to be processed according to the distribution of first micropores of the third aperture.
[0101] See also Figure 8a-8b The material of the substrate 111a to be processed is glass, which can be one or more of borosilicate glass, quartz glass and photosensitive lithium aluminosilicate glass. The substrate 111a to be processed includes a first surface 1111a and a second surface 1111b opposite to the first surface 1111a. The substrate 111a to be processed is irradiated for the first time with an infrared picosecond or femtosecond laser having a frequency of 100kHz-200kHz and a pulse width of less than 10 picoseconds according to a first aperture. In this step, the material of the substrate 111a to be processed within the first aperture range is induced by the laser and can be removed in a subsequent etching process.
[0102] S12: performing the first etching on the substrate subjected to the first laser induction, wherein the etching time is the total etching time (N) required for the first microhole of the first aperture minus the etching time (M) required for the second microhole of the second aperture.
[0103] Specifically, the substrate 111a to be processed after the first laser induction is immersed in a corrosion solution with a temperature of 30°C to 60°C. The corrosion solution can be an acidic corrosion solution, a hydrofluoric acid solution, or an alkaline corrosion solution, a sodium hydroxide solution. The corrosion rate of the laser-modified part is dozens of times greater than that of the unmodified part. Therefore, a prefabricated hole with a prefabricated aperture is formed on the substrate 111a to be processed, and the prefabricated hole passes through the first surface 1111a and the second surface 1111b.
[0104] Specifically, before the preparation, it is determined through experiments that it takes N minutes to etch the first micropore 113a with the first aperture, and it is determined that it takes M minutes to etch the second micropore 113b with the second aperture. Then, in this step, the first etching time is NM minutes. That is, N is the first etching time for forming the first micropore 113a with the first aperture, M is the second etching time for forming the second micropore 113b with the second aperture, and NM is the time difference between the first etching time for forming the first micropore 113a with the first aperture and the second etching time for forming the second micropore 113b with the second aperture.
[0105] In other specific embodiments, the first etching of the substrate 111a to be processed is performed by using etching methods such as spraying, stirring, and blowing, so that the etching solution is fully exchanged and flowed, and the side wall of the first micropore 113a etched is more uniform and smooth. Furthermore, the etching solution temperature is preheated to between 30°C and 60°C to accelerate the etching speed.
[0106] In a specific embodiment, after steps S11 and S12, a first micro-hole array 113c including a plurality of pre-formed holes with pre-formed hole diameters is formed on the substrate 111a to be processed.
[0107] S13: Laser induction is performed on the substrate to be processed according to the second aperture.
[0108] See also Figure 8c-8d , the substrate 111a to be processed that has been induced and etched by the first laser is irradiated for the second time according to the second aperture using an infrared picosecond or femtosecond laser with a frequency of 100kHz-200kHz and a pulse width of less than 10 picoseconds. The area irradiated for the second time is different from the area irradiated for the first time. In this step, the materials of the substrate 111a to be processed within the second aperture range are all induced by the laser and can be removed in the subsequent etching process.
[0109] S14: performing a second etching on the substrate subjected to the second laser induction for a time (M) required for etching the second microholes of the second aperture.
[0110] In this step, the substrate 111a to be processed after the second laser induction is immersed in the etching solution. After the immersion time M minutes, the second micropore 113b with the second aperture is formed on the substrate 111a to be processed, wherein the second etching process of the substrate 111a to be processed expands the prefabricated hole from the prefabricated aperture to the first aperture, forming the first micropore 113a. Specifically, after the substrate 111a to be processed is immersed in the etching solution twice, the thickness is reduced to a certain extent, and the first micropore 113a and the second micropore 113b penetrate the first surface 1111a and the second surface 1111b, thereby obtaining a liquid-conducting glass substrate 116 with liquid-conducting micropores 113 with different apertures. It can be understood that when the liquid-conducting glass substrate 116 is made of glass such as borosilicate glass, quartz glass or photosensitive lithium aluminosilicate glass or dense ceramics, it is a dense substrate 111.
[0111] In a specific embodiment, after steps S13 and S14, a second micropore array 113d including a plurality of second micropores 113b with a second pore size and a first micropore array 113c including a plurality of first micropores 113a with a first pore size are formed on the liquid-conducting glass substrate 116.
[0112] Since the dense matrix 111 in the heating element 11 is a dense material, it can play a role of structural support. Compared with the spring-shaped metal heating wire of the existing cotton core heating element and the metal thick film wire of the porous ceramic heating element, there is no requirement for the strength and thickness of the heating film 112 in the heating element 11, and the heating film 112 can be made of a metal material with low resistivity.
[0113] In one embodiment, the heating film 112 formed on the first surface 1111 of the dense substrate 111 is a thin film, and the thickness of the heating film 112 is in the range of 200 nanometers to 5 micrometers, that is, the thickness of the heating film 112 is relatively thin; preferably, the thickness of the heating film 112 is in the range of 200 nanometers to 1 micrometer; more preferably, the thickness of the heating film 112 is in the range of 200 nanometers to 500 nanometers. When the heating film 112 is a thin film, the micropores 113 penetrate the heating film 112. Furthermore, the heating film 112 is also formed on the inner surface of the micropores 113; preferably, the heating film 112 is also formed on the entire inner surface of the micropores 113 (structure as shown in FIG. Figure 3 A heating film 112 is provided on the inner surface of the micropore 113, so that the aerosol generating substrate can be atomized in the micropore 113, which is beneficial to improve the atomization effect.
[0114] The thinner the heating film 112 is, the smaller the impact on the aperture of the micropores 113 is, thereby achieving a better atomization effect; and the thinner the heating film 112 is, the less heat the heating film 112 itself absorbs, the lower the electric heat loss is, and the faster the heating element 11 heats up. On the basis that the resistance of the heating film 112 at room temperature is 0.5 ohms-2 ohms, this application uses a metal material with low conductivity to form a thinner metal film to minimize the impact on the aperture of the micropores 113. Optionally, the resistivity of the heating film 112 is not greater than 0.06*10 -6 Ω·m. The low-conductivity metal material of the heating film 112 includes silver and its alloys, copper and its alloys, aluminum and its alloys, gold and its alloys; optionally, the material of the heating film 112 may include aluminum and its alloys, gold and its alloys. When powered on for heating, the heating film 112 can heat up quickly, directly heat the aerosol-generating matrix in the micropores 113, and achieve efficient atomization.
[0115] Furthermore, the inventors of the present application have found that the liquid aerosol generation matrix contains various flavors and additives, including sulfur, phosphorus, chlorine and other elements. When the heating film 122 is electrically heated, silver and copper are prone to corrosion and failure. Gold has very strong chemical inertness, and a dense oxide film is formed on the surface of aluminum. These two materials are very stable in the liquid aerosol generation matrix and are preferably used as the heating film 122 material.
[0116] The heating film 112 can be formed on the first surface 1111 of the dense substrate 111 by physical vapor deposition (e.g., magnetron sputtering, vacuum evaporation, ion plating) or chemical vapor deposition (plasma-assisted chemical deposition, laser-assisted chemical deposition, metal organic compound deposition). It is understood that the formation process of the heating film 112 does not cover the micropores 113, that is, the micropores 113 penetrate the heating film 112. When the heating film 112 is formed on the first surface 1111 of the dense substrate 111 by physical vapor deposition or chemical vapor deposition, the heating film 112 is also formed on the inner surface of the micropores 113. When magnetron sputtering is used to form the heating film 112 on the first surface 1111 of the dense substrate 111, the metal atoms are perpendicular to the first surface 1111 and parallel to the inner surface of the micropore 113 during magnetron sputtering, and the metal atoms are more easily deposited on the first surface 1111; assuming that the thickness of the heating film 112 formed by the metal atoms deposited on the first surface 1111 is 1 micron, at this time, the thickness of the metal atoms deposited on the inner surface of the micropore 113 is much less than 1 micron, and even less than 0.5 microns; the thinner the heating film 112 deposited on the first surface 1111, the thinner the thickness of the heating film 112 formed on the inner surface of the micropore 113, and the smaller the impact on the aperture of the micropore 113. Since the thickness of the heating film 112 is much smaller than the aperture of the micropore 113, and the thickness of the portion of the heating film 112 deposited in the micropore 113 is smaller than the thickness of the portion deposited on the first surface 1111 of the dense matrix 111, the effect of the heating film 112 deposited in the micropore 113 on the aperture of the micropore 113 can be ignored.
[0117] In another embodiment, the heating film 112 formed on the first surface 1111 of the dense substrate 111 is a thick film, and the thickness of the heating film 112 ranges from 5 microns to 100 microns, preferably, from 5 microns to 50 microns. On the basis that the resistance of the heating film 112 is 0.5 ohms to 2 ohms, the material of the heating film 112 includes one of nickel-chromium alloy, nickel-chromium-iron alloy, iron-chromium-aluminum alloy, nickel, platinum, and titanium. The heating film 112 is formed on the first surface 1111 of the dense substrate 111 by printing; due to the low roughness of the first surface 1111 of the dense substrate 111, the thickness of the heating film 112 can form a continuous film below 100 microns. At this time, the first surface 1111 of the dense matrix 111 includes a microporous pattern area 1115 and a non-microporous pattern area 1116, and the heating film 112 is formed in the non-microporous pattern area 1116; that is, the micropores 113 are not provided at the heating film 112 on the first surface 1111 of the dense matrix 111, so as to ensure the stability and consistency of the heating film 112. (As shown in FIG. Figure 9a As shown, Figure 9a Schematic diagram of the top view of the structure when the heating film in the heating element provided in the present application is a thick film).
[0118] See also Figure 9b , Figure 9b yes Figure 3 A schematic diagram of the top view structure of the heating element is provided.
[0119] The shape of the heating film 112 can be sheet-like, mesh-like or strip-like. The sheet-like and strip-like in the present application refer to different aspect ratios of the heating film 112. An aspect ratio greater than 2 can be considered as a strip, and less than 2 can be considered as a sheet. Under the same conditions of material and thickness, the resistance of the strip-like heating film 112 is greater than the resistance of the sheet-like heating film 112. When the heating film 112 is sheet-like, the heating film 112 can cover the entire first surface 1111, and the temperature field formed on the first surface 1111 of the dense matrix 111 is uniform; since the aerosol generating matrix usually contains multiple components, the temperature field is uniform, which is not conducive to the reduction of the aerosol generating matrix. When the heating film 112 is in a strip shape, the heating film 112 only covers part of the first surface 1111, and the heating film 112 forms a temperature field with a gradient on the first surface 1111 of the dense matrix 111. The gradient temperature field includes the boiling point temperatures of different components in the aerosol generating matrix, which can make each component in the aerosol generating matrix atomized at its boiling point, achieve a better atomization effect, and help improve the reduction degree of the aerosol generating matrix. When the heating film 112 is in a mesh shape, the size of the grid determines whether the temperature field formed by the heating film 112 on the first surface 1111 of the dense matrix 111 is uniform, and the size of the grid is designed according to needs; even if the size of the grid is set to enable the heating film 112 to form a temperature field with a temperature gradient on the first surface 1111 of the dense matrix 111, its atomization effect is not as good as when the heating film 112 is in a strip shape.
[0120] In other embodiments, when the heating film 112 is in sheet form, the heating film 112 can cover the entire first surface 1111, and the heating film 112 can form a temperature field with a gradient on the first surface 1111 of the dense substrate 111 by making the thickness of the heating film 112 in different regions uneven or using different materials of the heating film 112 in different regions. It can be understood that by depositing the heating film 112 by physical vapor deposition or chemical vapor deposition and adjusting the positional relationship between the dense substrate 111 and the material source, it is easy to realize a heating film 112 with a gradient thickness.
[0121] The heating film 112 is introduced as a strip, and the structure is as follows Figure 9bAs shown. The dense matrix 111 is in the shape of a rectangular plate, and the heating film 112 includes a heating film body 1121 and an electrode 1122. The electrode 1122 includes a positive electrode and a negative electrode. In order to achieve a better atomization effect, the heating film body 1121 is designed to be an S-shaped curved strip to form a temperature field with a temperature gradient on the first surface 1111 of the dense matrix 111, that is, a high temperature zone and a low temperature zone are formed on the first surface 1111 of the dense matrix 111, so as to atomize the various components in the aerosol generating matrix to the maximum extent. One end of the heating film body 1121 is connected to the positive electrode, and the other end is connected to the negative electrode. The size of the electrode 1122 is larger than that of the heating film body 1121, so that the electrode 1122 can be better electrically connected to the power supply component 2. In this embodiment, the heating film body 1121 and the electrode 1122 are integrally formed, that is, the heating film body 1121 and the electrode 1122 are made of the same material; in other embodiments, the heating film body 1121 and the electrode 1122 may be made of different materials as long as their functions can be achieved.
[0122] The inventors of the present application have found that since the strip heating film 112 is a strip-shaped and slender structure, its resistance is greater than that of the sheet heating film 112 under the same conditions. Therefore, in order to prepare a strip heating film 112 with a thickness of nanometer level, especially a thickness of 200 nanometers to 500 nanometers, the material of the heating film 112 can only be selected from materials such as aluminum, gold, silver and copper whose resistivity is not more than 0.03*10-6Ω·m.
[0123] The first surface 1111 of the dense matrix 111 includes a microporous area 1117 and a non-microporous area 1118, the electrode 1122 is arranged in the non-microporous area 1118, and the heating film body 1121 is arranged in the microporous area 1117. Figure 9b The heating film 112 shown is a thin film, and some micropores 113 penetrate the heating film body 1121 .
[0124] It can be understood that when the apertures of the multiple micropores 113 arranged on the dense matrix 111 are different, the micropore area 1117 includes a first aperture micropore array area 1113 and a second aperture micropore array area 1114, the apertures of the micropores 113 in the first aperture micropore array area 1113 are the same, the apertures of the micropores 113 in the second aperture micropore array area 1114 are the same, and the apertures of the micropores 113 in the first aperture micropore array area 1113 are different from the apertures of the micropores 113 in the second aperture micropore array area 1114, and the specific design is based on needs. When the heating film 112 formed on the first surface 1111 of the dense substrate 111 is a thick film, the heating film body 1121 is arranged in the microporous area 1117, and the electrode 1122 is arranged in the non-microporous area 1118; due to the process conditions for forming the thick film heating film 112, the microporous area 1117 is provided with the heating film body 1121 where the micropores 113 are not arranged; that is, the microporous area 1117 includes a microporous pattern area 1115 and a non-microporous pattern area 1116, and the heating film body 1121 is arranged in the non-microporous pattern area 1116.
[0125] As mentioned above, in order to prepare a heating film 112 with a thickness of less than 5 microns or even at the nanometer level, aluminum, gold, silver and copper become the preferred materials. However, the heating film 112 made of silver and copper is easily corroded and fails in the liquid aerosol generation matrix. In addition, the heating film 112 made of aluminum also has the risk of failure after long-term high-power use. To this end, the inventors of the present application studied the protective layer of the heating film 112 and found that the existing oxide and nitride protective layers, such as silicon dioxide, have a large difference in thermal expansion coefficient from metals, and the internal stress between the film layers during thermal cycles will cause the protective layer to fail rapidly. Moreover, oxides and nitrides have poor conductivity. As a protective layer, if the heating film and the electrode are covered, the electrical contact effect between the electrode and the lead or the ejector pin will be caused; if the electrode is not covered, the preparation process is complicated. In order to solve the above problems, the present application provides a protective film 115 further provided on the heating film 112 of the heating element 11.
[0126] See also Fig.10 and Fig.11 , Fig.10 It is a partial structural schematic diagram of the heating element provided by the present application, including a protective film and the heating film is a thin film, Fig.11 It is a schematic diagram of a top view structure in which the heating element provided in the present application includes a protective film and the heating film is a thick film.
[0127] Furthermore, the heating element 11 further includes a protective film 115. The protective film 115 is formed on the surface of the heating film 112 away from the dense substrate 111, and the material of the protective film 115 is a metal alloy resistant to corrosion by the aerosol generating matrix, so as to prevent the aerosol generating matrix from corroding the heating film 112, thereby protecting the heating film 112 and improving the performance of the electronic atomization device.
[0128] When the heating film 112 is a thin film (structure such as Fig.10 As shown), the thickness of the heating film 112 is 200 nanometers to 5 micrometers, and the resistivity of the heating film 112 is not greater than 0.06*10 -6 Ω·m, the material of the heating film 112 is copper and its alloys, silver and its alloys, aluminum and its alloys, gold and its alloys, and the heating film 112 is formed on the first surface 1111 of the dense substrate 111 by physical vapor deposition or chemical vapor deposition; optionally, the material of the heating film 112 is one of copper, silver, aluminum, gold, aluminum alloy, and aluminum-gold alloy. The thickness of the protective film 115 is 100 nanometers to 1000 nanometers, and the material of the protective film 115 is one of stainless steel, nickel-chromium-iron alloy, and nickel-based corrosion-resistant alloy; wherein the stainless steel can be 304 stainless steel, 316L stainless steel, 317L stainless steel, 904L stainless steel, etc., the nickel-chromium-iron alloy can be inconel625, inconel718, etc., and the nickel-based corrosion-resistant alloy can be nickel-molybdenum alloy B-2, nickel-chromium-molybdenum alloy C-276, etc. Preferably, the material of the protective film 115 is stainless steel. The protective film 115 is formed on the surface of the heating film 112 away from the dense matrix 111 by physical vapor deposition (e.g., magnetron sputtering, vacuum evaporation, ion plating) or chemical vapor deposition (plasma assisted chemical deposition, laser assisted chemical deposition, metal organic compound deposition). It can be understood that the formation process of the heating film 112 and the protective film 115 does not cover the micropores 113, that is, the micropores 113 penetrate the heating film 112 and the protective film 115. Since the protective film 115 can effectively prevent the aerosol-generated matrix from corroding the heating film 112, the material of the heating film 112 can be copper and silver, so as to prepare a nano-scale heating film 112.
[0129] When the heating film 112 is a thick film (structure such as Fig.11As shown), the thickness of the heating film 112 is 5 microns to 100 microns, and the material of the heating film 112 is one of nickel-chromium alloy, nickel-chromium-iron alloy, iron-chromium-aluminum alloy, gold, silver, nickel, platinum, and titanium. The thickness of the protective film 115 is 5 microns to 20 microns, and the material of the protective film 115 is one of stainless steel, nickel-chromium-iron alloy, and nickel-based corrosion-resistant alloy; wherein the stainless steel can be 304 stainless steel, 316L stainless steel, 317L stainless steel, 904L stainless steel, etc., the nickel-chromium-iron alloy can be inconel625, inconel718, etc., and the nickel-based corrosion-resistant alloy can be nickel-molybdenum alloy B-2, nickel-chromium-molybdenum alloy C-276, etc. Preferably, the material of the protective film 115 is stainless steel. When the heating film 112 and the protective film 115 are formed on the first surface 1111 of the dense substrate 111 in sequence by printing, the material of the heating film 112 is one of nickel-chromium alloy, nickel-chromium-iron alloy, iron-chromium-aluminum alloy, nickel, platinum, and titanium, and the material of the protective film 115 is stainless steel; when the heating film 112 is formed on the first surface 1111 of the dense substrate 111 by printing, and the protective film 115 is formed on the surface of the heating film 112 away from the dense substrate 111 by physical vapor deposition or chemical vapor deposition, the material of the heating film 112 is one of nickel-chromium alloy, nickel-chromium-iron alloy, iron-chromium-aluminum alloy, nickel, platinum, and titanium, and the material of the protective film 115 is one of stainless steel, nickel-chromium-iron alloy, and nickel-based corrosion-resistant alloy. By setting the protective film 115 on the surface of the thick film heating film 112, it is possible to prevent the aerosol-generated matrix from corroding the heating film 112.
[0130] The protective film 115 is disposed on the surface of the heating film 112. The protective film 115 is a metal alloy. Theoretically, when the heating film 112 is heating, the protective film 115 is also heating. Since the resistance of the protective film 115 is much greater than that of the heating film 112, the protective film 115 hardly generates heat, and the heating film 112 mainly heats the atomized aerosol to generate the matrix. For example, the resistance of the heating film 112 is about 1 ohm, and the protective film 115 is made of stainless steel, and the resistance of the protective film 115 is about 30 ohms. The resistance of the protective film 115 is too large, and the resistance of the protective film 115 is much greater than that of the heating film 112. Under the conditions that the power of the electronic atomization device is 6 watts to 8.5 watts and the voltage of the battery is 2.5 volts to 4.4 volts, the protective film 115 cannot play the role of the heating film 112, that is, the protective film 115 cannot heat the atomized aerosol to generate the matrix.
[0131] In the present application, the heating film 112 includes a heating film body 1121 and an electrode 1122. The heating film body 1121 and the electrode 1122 are made of the same material, and the protective film 115 is disposed on the surfaces of the heating film body 1121 and the electrode 1122. It can be understood that the protective film 115 is formed only on the heating film body 1121, and the protective film 115 is not disposed on the electrode 1122, so as to reduce the resistance of the electrode 1122, and further reduce the resistance consumption between the electrode 1122 and the ejector pin of the power supply component 2, that is, the protective film 115 exposes part of the heating film 112 to serve as the electrode 1122 of the heating film 112; further, the electrode 1122 can be set to a material different from that of the heating film body 1121, so that the resistance of the electrode 1122 is lower, so as to reduce the resistance consumption between the electrode 1122 and the ejector pin of the power supply component 2.
[0132] It is understandable that the thickness of the dense matrix 111, the pore size of the micropores 113, the ratio of the thickness of the dense matrix 111 to the pore size of the micropores 113, and the ratio of the center distance of adjacent micropores 113 to the pore size of the micropores 113 provided in the present application can be combined and designed as needed; the dense matrix 111 can be combined with the thin film heating film 112 (the thickness of the heating film 112 is 200 nanometers to 5 micrometers, and the resistivity of the heating film 112 is not greater than 0.06*10 -6 Ω·m, the material of the heating film 112 is copper and its alloy, silver and its alloy, aluminum and its alloy, gold and its alloy) or thick film heating film 112 (the thickness of the heating film 112 is 5 microns-100 microns, and the material of the heating film 112 is one of nickel-chromium alloy, nickel-chromium-iron alloy, iron-chromium-aluminum alloy, nickel, platinum, and titanium) can be combined and designed as needed; the protective film 115 can be designed as needed. The protective film 115 in the heating element 11 provided in the present application can be applied to the surface of a traditional porous ceramic heating element to protect its heating film.
[0133] See also Fig.12 , Fig.12 It is a schematic diagram of the partial structure of the atomization assembly provided in the present application including a loose matrix.
[0134] Furthermore, the atomization assembly 1 also includes a loose matrix 114, which is arranged on the second surface 1112 of the dense matrix 111 of the heating element 11. The loose matrix 114 can be a material such as porous ceramics, sponges, foams, fiber layers, etc., which can achieve the effects of liquid storage, liquid conduction, and heat insulation. In other words, the aerosol generating matrix in the liquid storage chamber 10 is first guided to the second surface 1112 of the dense matrix 111 through the loose matrix 114, and then guided to the first surface 1111 of the dense matrix 111 through the micropores 113 on the dense matrix 111 to be atomized by the heating film 112.
[0135] The following experiments verify the effects of the arrangement of the micropores 113 on the dense substrate 111, the selection of the material of the heating film 112, and the protective film 115 provided in the present application.
[0136] Experiment 1: Material selection when the heating film 112 is a thin film.
[0137] Take the common heating film 112 pattern in this industry as an example (such as Figure 9b The shape of the heating film 112 is shown), the length of the heating film 112 is 8.5 mm, the width is 0.4 mm, and the resistance is 1 ohm at room temperature. The heating film 112 is made of different materials. The theoretical thickness of the required heating film 112 can be obtained according to the resistivity of different metal materials. The results are shown in Table 1.
[0138] Table 1. Resistivity of metal materials and theoretical thickness of heating film
[0139]
[0140] According to Table 1, when using traditional nickel-chromium alloy, nickel-chromium-iron alloy, and iron-chromium-aluminum alloy, the theoretical thickness of the heating film 112 needs to be more than 20μm, which will seriously affect the atomization efficiency. During the deposition process, it will also cause the aperture of the micropores 113 in the dense matrix 111 to shrink, affecting the supply and atomization of the aerosol generation matrix. When using low-resistivity metal materials such as silver, copper, gold, and aluminum, the theoretical thickness of the heating film 112 is less than 1μm, which not only has no effect on the aperture of the micropores 113 in the dense matrix 111, but also reduces the energy absorbed by the heating film 112 during atomization. In addition, the thermal conductivity of materials such as silver, copper, gold, and aluminum is much higher than that of nickel-chromium alloy, nickel-chromium-iron alloy, and iron-chromium-aluminum alloy, which is conducive to rapid heat conduction and enhanced atomization efficiency.
[0141] The heating film 112 made of silver, copper, gold, aluminum and other materials can work stably for a long time in the PG / VG mixture (propylene glycol / glycerol mixture), but the aerosol generation matrix also contains various flavors and additives, and these flavors and additives contain sulfur, phosphorus, chlorine and other elements, which may cause corrosion to the heating film 112. Through experiments, it was found that when silver is used as the material of the heating film 112, the resistance of the heating film 112 will continue to increase during the wet burning heat cycle, and the heating film 112 will fail after about 30 puffs; because copper is more resistant to chloride ions, when copper is used as the material of the heating film 112, the resistance of the heating film 112 will still increase during the wet burning heat cycle, but the life of the heating film 112 can be extended to about 80 times; aluminum is more stable in the environment of the aerosol generation matrix, and a dense oxide film structure can be formed on the surface, which can withstand more than 600 times during the thermal cycle; and gold, as the metal with the most stable chemical properties, is more stable and reliable in the thermal cycle, and the thermal cycle resistance remains unchanged after more than 1500 times.
[0142] Therefore, when the material of the heating film 112 is silver or copper, the heating film 112 is prone to corrosion failure when electrically heated; since gold has very strong chemical inertness, a dense oxide film will be generated on the surface of aluminum, and the heating film 112 formed of gold or aluminum is very stable in the aerosol generating matrix and is not prone to corrosion when the heating film 112 is electrically heated. Therefore, when the heating element 11 does not include the protective film 115, the material of the heating film 112 is aluminum and its alloys, gold and its alloys; when the heating element 11 includes the protective film 115, the protective film 115 can prevent the heating element 11 from being corroded by the aerosol generating matrix, and there is no requirement for the material of the heating element 11. The material of the heating film 112 is silver and its alloys, copper and its alloys, aluminum and its alloys, gold and its alloys.
[0143] Aluminum is selected as the material of the heating film 112, and is deposited on the first surface 1111 of the dense substrate 111 by magnetron sputtering. The thickness of the deposition is 3 microns. The obtained SEM image is as follows: Fig.13 As shown ( Fig.13 is a SEM image of an embodiment of the heating film provided by the present application). Fig.13 It can be seen that the deposition thickness of the heating film 112 is 3 micrometers, and the heating film 112 is also deposited on the inner surface of the micropore 113 , but has no obvious effect on the pore size of the micropore 113 .
[0144] The heating element 11 provided by the present application and the conventional porous ceramic heating element were subjected to a wet burning experiment at 6.5 watts to obtain the respective atomized aerosol amounts, and the results were compared as follows: Fig.14 The results shown ( Fig.14 The figure is a comparison of the amount of atomized aerosol of the heating element of the present application and the conventional porous ceramic heating element); wherein the heating element 11 of the present application and the conventional porous ceramic heating element have a porosity of 57%-61%, a thickness of 1.6mm, and a pore size of 15-50μm. Fig.14 It can be seen that the aerosol amount of the heating element 11 of the present application is still stable after 650 wet-firing times, while the aerosol amount of the traditional porous ceramic heating element begins to decrease significantly after 650 wet-firing times; under the same number of wet-firing times, the aerosol amount atomized by the heating element 11 provided by the present application is greater than the aerosol amount atomized by the traditional porous ceramic heating element, that is, the heating element 11 provided by the present application can achieve efficient atomization.
[0145] Experiment 2: Verify the function of the protective film 115 provided in this application.
[0146] The life of the heating element 11 is evaluated by wet burning the heating element 11. Experimental conditions: 6.5 watts of constant power supply, a mode of puffing for 3 seconds and stopping for 27 seconds, the aerosol generation matrix is mint flavor, nicotine content is 50 mg / 100 ml, and the thickness of the heating film 112 is 1-2 microns; wherein, the heating element 11 is provided with a protective film 115 and is not provided with a protective film 115. The protective film 115 is compared with different materials, and the normal use environment of the electronic atomization device is simulated for the experiment. The comparison results are shown in Table 2, and the relationship between the heating film 112 material and the protective film 115 material and the life of the heating element 11 is obtained.
[0147] Table 2. Relationship between heating film material, protective layer material and heating element life
[0148]
[0149] In Table 2, the thickness of the protective film 115 of silicon dioxide is 30nm, the thickness of the protective film 115 of titanium nitride is 100nm, and the thickness of the protective film 115 of 316L stainless steel is 800nm. According to Table 2, when silver and copper are used as the material of the heating film 112, they are easily corroded by flavors and additives containing sulfur, phosphorus, chlorine and other elements in the aerosol generation matrix, and it is difficult to meet the life requirements; when aluminum is used as the material of the heating film 112, it can withstand more than 600 thermal cycles, which meets the use conditions of most electronic atomization devices (the power of the electronic atomization device is 6 watts-8.5 watts), but it is difficult to meet the requirements of more than 1500 times when the power of the electronic atomization device is greater than 10 watts.
[0150] When silicon dioxide is used as the material of the protective film 115, due to the large difference in thermal expansion coefficients between silicon dioxide and metal, the internal stress between the film layers during thermal cycling will cause the protective film 115 to fail quickly, making it difficult to play a protective role. It is understandable that when zirconium oxide and aluminum oxide are used as the protective film 115, the thermal expansion coefficients of zirconium oxide and aluminum oxide are too large compared to metals, and they are prone to failure and difficult to play a protective role.
[0151] Titanium nitride is a commonly used protective coating. This application uses copper as the material of the heating film 112 to verify whether titanium nitride is suitable for the protective film 115. During the wet firing process, the resistance of the heating film 112 increases continuously, and the heating film 112 fails after 130 thermal cycles (e.g. Fig.15 As shown, Fig.15 1 is a failure diagram of the heating film in the heating element provided by the present application). Through optical microscope observation, it is found that the heating film 112 is severely corroded and falls off from the dense matrix 111. Fig.16 ( Fig.16 yes Fig.15It can be found from the SEM image and EDS image of the heating film failure image provided that the titanium nitride layer on the surface of the heating film 112 has been basically completely corroded, exposing the copper layer of the heating film 112, and the copper layer has also been severely corroded, exposing the dense matrix 111 in some areas. That is to say, in this application, the protective film 115 made of titanium nitride is also easily corroded by the aerosol-generating matrix.
[0152] When stainless steel is used as the material of the protective film 115, the heating film 112 can withstand more than 1500 thermal cycles regardless of whether the material is silver, copper or aluminum, which can greatly increase the life of the heating element 11. In addition, experiments have shown that metals with a high nickel content can protect the heating film 112.
[0153] Therefore, the present application adopts corrosion-resistant stainless steel (304, 316L, 317L, 904L, etc.), nickel-chromium-iron alloy (inconel625, inconel718, etc.), nickel-based corrosion-resistant alloy (nickel-molybdenum alloy B-2, nickel-chromium-molybdenum alloy C-276), etc. as the material of the protective film 115 to improve the life of the heating element 11. Regardless of whether the material of the heating film 112 is silver, copper or aluminum, the use of the protective film 115 can greatly improve the life of the heating element 11.
[0154] The life of the heating film 112 increases with the thickness of the protective film 115. Fig.17 As shown ( Fig.17 is a graph showing the relationship between the life of the heating film and the thickness of the protective film in the heating element provided by the present application). Fig.17 It can be seen that when the aerosol generating matrix uses 50 mg of mint and the material of the protective film 115 is S316L stainless steel, as the thickness of the protective film 115 increases, the resistance change of the heating film 112 becomes smaller and the life of the heating film 112 becomes longer.
[0155] Experiment 3: Effects of the thickness of the dense matrix 111 and the pore size of the micropores 113 on the liquid supply efficiency.
[0156] The liquid supply efficiency of the heating element 11 is evaluated by a wet burning test of the heating element 11. The principle of the wet burning test is as follows: Fig.18 As shown ( Fig.18 Schematic diagram of the wet burning experiment of the heating element provided in the present application). A DC power supply is used to supply power, and the electrodes 1122 of the heating film 112 are respectively connected through the ejector pins 20 of the power supply assembly 2 (the ejector pins 20 are electrically connected to the battery), and the power supply power and power supply time are controlled. The temperature of the heating film 112 is measured using an infrared thermal imager or a thermocouple.
[0157] When the heating film 112 is powered on, the temperature rises instantly, causing the aerosol generating matrix in the micropores 113 to vaporize. As the aerosol generating matrix in the micropores 113 is consumed, the capillary action of the micropores 113 causes the aerosol generating matrix in the liquid storage chamber 10 to be continuously replenished to the heating film 112 .
[0158] The flow of the aerosol-generating substrate in the micropores 113 with capillary action can be calculated according to the Washburn equation, where S is the pore area of the micropores 113, ρ is the density of the aerosol-generating substrate, z is the distance traveled by the aerosol-generating substrate, γ is the surface tension, μ is the viscosity of the aerosol-generating substrate, r is the radius of the micropores 113, and θ is the contact angle of the aerosol-generating substrate to the dense matrix 111 material. The atomization amount of the aerosol-generating substrate is as follows:
[0159]
[0160] It can be seen from the formula that after determining the materials of the aerosol generating matrix and the dense matrix 111, ρ, γ, μ, and θ remain unchanged. The larger the aperture of the micropore 113, the more sufficient the liquid supply, but the risk of leakage due to aviation negative pressure during transportation and warm shock during use will also be greater. Therefore, the thickness, aperture, and thickness-to-diameter ratio of the dense matrix 111 are very important, both to ensure sufficient liquid supply during the atomization process and to prevent leakage of the aerosol generating matrix.
[0161] The heating element 11 was installed and tested to evaluate the relationship between the thickness of the dense matrix 111 / the diameter of the micropores 113 and the amount of atomization. The results are as follows: Fig.19 As shown ( Fig.19 is a graph showing the relationship between the thickness of the dense matrix / pore diameter of the heating element and the amount of atomization provided by the present application). Fig.19 It can be seen that when the thickness of the dense matrix 111 / the aperture of the micropores 113 is too large, the aerosol-generating matrix supplied by capillary action is difficult to meet the atomization demand, and the atomization amount decreases. When the thickness of the dense matrix 111 / the aperture of the micropores 113 is too small, the aerosol-generating matrix is easy to flow out of the micropores 113 to the surface of the heating film 112, resulting in a decrease in atomization efficiency and a decrease in atomization amount.
[0162] Experiment 4: Comparison of the performance of the heating element 11 provided in the present application and the traditional porous ceramic heating element.
[0163] If the aerosol generating substrate is adequately supplied, the temperature of the heating film 112 will be maintained near the boiling point of the aerosol generating substrate in a thermal equilibrium state; if the aerosol generating substrate is insufficiently supplied, dry burning will occur, and the temperature of the heating film 112 will be higher than the boiling point of the aerosol generating substrate. Therefore, the liquid supply efficiency of the heating element 11 can be evaluated by the wet burning experiment of the heating element 11.
[0164] The dense matrix 111 of the heating element 11 provided in the present application has a thickness of 0.2 mm and a pore size of 30 μm. The heating element 11 is compared with a conventional porous ceramic heating element (porosity of 57%-61%, thickness of 1.6 mm, pore size of 15-50 μm).
[0165] For the traditional porous ceramic heating element, under the condition of 6.5W power, the temperature of the heating film instantly rises to about 270℃ after power is turned on. During the 3-second heating duration, the temperature is almost stable and reaches a thermal equilibrium state. However, as the heating power increases, the temperature of the heating film in the thermal equilibrium state continues to rise, indicating that the porous ceramic structure that undertakes the liquid conduction function is insufficiently supplied with liquid. Fig. 20 As shown ( Fig. 20 is the relationship between the atomization temperature and heating power of the traditional porous ceramic heating element).
[0166] In contrast, when the heating element 11 is used, the thickness of the dense matrix 111 is 0.2 mm, the pore size of the micropores 113 is 30 μm, and the power is in the range of 6.5 W to 11.5 W, the temperature of the heating film 112 in the thermal equilibrium state is around 250° C. Fig.21 As shown ( Fig.21 is a relationship diagram between the atomization temperature and the heating power of the heating element provided in the present application); it indicates that the dense matrix 111 of the structure is adequately supplied with liquid, and no leakage was found in the experiment.
[0167] Under the condition of heating power of 6.5W, the relationship between the atomization temperature and the puffing time of the heating element 11 provided in the present application was studied. The results are as follows Fig. 22 As shown ( Fig. 22 is a graph showing the relationship between the atomization temperature of the heating element and the puffing time provided by the present application). Fig. 22 It can be seen that as the heating time increases, the atomization temperature of the heating element 11 provided in the present application remains stable in the thermal equilibrium state; this indicates that as the aerosol generating matrix in the micropores 113 is continuously consumed, when boiling atomization occurs, the aerosol generating matrix in the liquid storage chamber 10 can be continuously supplied to meet the atomization demand and ensure the atomization amount.
[0168] The beneficial effects of the present application are different from those of the prior art. The heating element in the present application includes a liquid-conducting glass substrate and a heating film; the specific preparation method includes: performing a first laser induction and corrosion on the substrate to be processed to form a prefabricated hole of the first micropore, and the prefabricated hole has a prefabricated aperture; performing a second laser induction and corrosion on the substrate to be processed to form a second micropore, and the second micropore has a second aperture, wherein the process of performing the second corrosion on the substrate to be processed expands the prefabricated aperture to the first aperture, and the prefabricated hole is transformed into the first micropore, thereby obtaining a liquid-conducting glass substrate with liquid-conducting micropores of different apertures; and forming a heating film on the first surface of the liquid-conducting glass substrate. Through the above process, the porosity of the heating element can be accurately controlled in batch production, the fluctuation range is small, and the heating power can be accurately matched, thereby achieving a better atomization effect, which is suitable for mass standardized production. In addition, since the process of performing the second corrosion on the substrate to be processed expands the first micropore from the prefabricated aperture to the first aperture, compared with separately preparing the second micropore with the second aperture and the first micropore with the first aperture, the method has a simple process and low cost.
[0169] The above description is only an implementation method of the present application, and does not limit the patent scope of the present application. Any equivalent structure or equivalent process transformation made using the contents of the present application specification and drawings, or directly or indirectly used in other related technical fields, are also included in the patent protection scope of the present application.
Claims
1. A method for preparing a liquid-conducting glass substrate, wherein the liquid-conducting glass substrate is used to heat and atomize a liquid aerosol to generate a matrix, characterized in that: The preparation method comprises: Performing a first laser induction and etching on the substrate to be processed to form a prefabricated hole of a first microhole, wherein the prefabricated hole has a prefabricated aperture; The substrate to be processed is subjected to a second laser induction and etching to form a second micropore, wherein the second micropore has a second aperture, wherein the second etching process of the substrate to be processed causes the prefabricated aperture to expand to the first aperture, and the prefabricated hole is transformed into the first micropore, thereby obtaining a liquid-conducting glass substrate having liquid-conducting micropores with different apertures.
2. The method for preparing a liquid-conducting glass substrate according to claim 1, characterized in that: The substrate to be processed includes a first surface and a second surface opposite to and parallel to the first surface. The first micropores and the second micropores are straight through holes penetrating and perpendicular to the first surface and the second surface.
3. The method for preparing a liquid-conducting glass substrate according to claim 1, characterized in that: The step of performing a first laser induction and etching on the substrate to be processed to form a prefabricated hole of the first micropore comprises: performing laser induction on the substrate to be processed according to the distribution of micropores of the first aperture; performing a first etching on the substrate subjected to the first laser induction, wherein the etching time is the total etching time (N) required for the first aperture minus the etching time (M) required for the second aperture; The step of performing a second laser induction and etching on the substrate to be processed to form the second micropores includes: performing laser induction on the substrate to be processed according to the distribution of micropores of a second aperture, and performing a second etching on the substrate subjected to the second laser induction for a time equal to the etching time (M) required for the second aperture.
4. The method for preparing a liquid-conducting glass substrate according to claim 1, characterized in that: The step of performing a first laser induction and etching on the substrate to be processed to form a preformed hole of the first microhole comprises: forming a preformed hole array including a plurality of preformed holes having the preformed hole diameter; The step of performing a second laser induction and etching on the substrate to be processed to form second micropores includes: forming a second micropore array including a plurality of second micropores with the second aperture and a first micropore array including a plurality of first micropores with the first aperture.
5. The method for preparing a liquid-conducting glass substrate according to claim 1, characterized in that: The ratio of the thickness of the liquid-conducting glass substrate to the pore size of the liquid-conducting micropores is 20:1-3:
1.
6. The method for preparing a liquid-conducting glass substrate according to claim 5, characterized in that: The ratio of the thickness of the liquid-conducting glass substrate to the pore size of the liquid-conducting micropores is 15:1-5:
1.
7. The method for preparing a liquid-conducting glass substrate according to claim 1, characterized in that: The ratio of the hole center distance between two adjacent liquid-conducting micropores to the hole diameter of the liquid-conducting micropores is 3:1-1.5:
1.
8. The method for preparing a liquid-conducting glass substrate according to claim 1, characterized in that: The substrate to be processed is glass.
9. The method for preparing a liquid-conducting glass substrate according to claim 8, characterized in that: The substrate to be processed is glass, and the glass is one or more of borosilicate glass, quartz glass and photosensitive lithium aluminosilicate glass.
10. A method for preparing a heating element for heating atomized liquid aerosol to generate a substrate, characterized in that: The preparation method comprises: Prepare a liquid-conducting glass substrate, wherein the preparation method of the liquid-conducting glass substrate is the preparation method according to any one of claims 1 to 9; A heat-generating film is formed on the first surface of the liquid-conducting glass substrate.
11. The method for preparing a heating element according to claim 10, characterized in that: The step of forming a heating film on the first surface of the liquid-conducting glass substrate includes: forming a heating film with a resistance of 0.5 ohms to 2 ohms and a thickness of 200 nanometers to 5 microns by physical vapor deposition or chemical vapor deposition; the material of the heating film is aluminum, copper, silver, gold or their alloys.
12. The method for preparing a heating element according to claim 11, characterized in that: After the step of forming a heating film on the first surface of the liquid-conducting glass substrate, the step includes: forming a protective film with a thickness of 100 nanometers to 1000 nanometers on the surface of the heating film away from the liquid-conducting glass substrate by physical vapor deposition or chemical vapor deposition; the material of the protective film is one or any combination of stainless steel, nickel-chromium-iron alloy, and nickel-based corrosion-resistant alloy.
13. The method for preparing a heating element according to claim 10, characterized in that: The step of forming a heating film on the first surface of the liquid-conducting glass substrate includes: forming a heating film with a resistance of 0.5 ohms to 2 ohms and a thickness of 5 microns to 100 microns by printing or chemical vapor deposition; the material of the heating film is one of nickel-chromium alloy, nickel-chromium-iron alloy, iron-chromium-aluminum alloy, nickel, platinum and titanium.
14. The method for preparing a heating element according to claim 13, characterized in that: After the step of forming a heating film on the first surface of the liquid-conducting glass substrate, the step includes: forming a protective film with a thickness of 5 microns to 20 microns on the surface of the heating film away from the liquid-conducting glass substrate by printing or chemical vapor deposition; the material of the protective film is stainless steel.
Citation Information
Patent Citations
Methods to fabricate a photoactive substrate suitable for microfabrication
CN102869630A
Electronic atomization device and atomizer and heating body thereof
CN111109665A